Prevalence of iron-deficient but non-anemic university athletes in Japan: an observational cohort study - Takahiro Nabeyama; Yosuke Suzuki; Hiroaki Saito; Kana Yamamoto; Michiko Sakane; Yoichiro Sasaki; Haruka Shindo; Morihito Takita; Masahiro Kami (Taylor & Francis Group, 2023)
ABSTRACTBackground Iron deficiency (ID) and iron deficiency anemia (IDA) are long-standing health problems in athletes, affecting both performance and health. ID prevalence in young athletes remains high and a matter of concern. ID and IDA can lead to fatigue, reduced endurance, and decreased oxygen transport, potentially compromising athletic performance. We hypothesized that ID would still be a major health concern in university athletes across sports clubs in Japan.Purpose The study aimed to investigate the prevalence of ID and IDA in athletes participating in Kendo, badminton, baseball, and handball at the University of Tsukuba (Tsukuba, Ibaraki Prefecture, Japan). The study also examined the correlation between hypoferritinemia and other variables, such as previous use of iron supplements, body mass index (BMI), energy intake, and years of athletics.Methods Between January and December 2019, 126 university athletes, consisting of 79 males and 47 females, underwent physical measurements and blood tests. The blood test included complete blood count, levels of serum ferritin, serum iron, and total iron-binding capacity. The anemia was defined in accordance with the WHO criteria. Daily energy and iron intake were estimated with the food frequency questionnaire in Japanese (FFQg). Thirty-four female athletes responded to a survey about their menstruation and low-dose estrogen-progestin (LEP) usage.Results While none of the athletes had anemia, 22 (47%) female athletes exhibited serum ferritin levels of 30 ng/mL or less, defining them as hypoferritinemia. The multivariate logistic regression model revealed that a shorter duration of the athletic experience (adjusted odd ratio [95% confidence interval]: 0.62 [0.43-0.90]), lower energy intake (0.994 [0.989-0.999]), and higher dietary iron intake (4.40 [1.12-17.26]) were associated with hypoferritinemia. Seventeen (50%) female athletes reported a decline in subjective performance during menstruation, albeit two took LEP regularly.Conclusions This study reveals that ID is a prevalent health concern among young female athletes across sports clubs. It underscores the need for their education on the importance of assessing ID status. Limitation includes the nature of single-site and observational study, the absence of hepcidin measurement, and an unspecified amount of exercise. Comprehensive investigations are needed to elucidate the causes and optimal treatments for ID in young athletes.